The Treatment of Polysemy and Homonymy in Monolingual General-purpose Dictionaries with Special Reference to Isichazamazwi SesiNdebele - Ndlovu, Eventhough; Sayi, Sanelisiwe (Lexikos, 2010)
ABSTRACT: This article focuses on the treatment of polysemy and homonymy in general-purpose monolingual dictionaries with special reference to Isichazamazwi SesiNdebele. It was found that there are some inconsistencies in the treatment of polysemous and homonymous entries in this dictionary. The article shows that an overreliance on one criterion, particularly etymology, to distinguish polysemy and homonymy is often misleading and unreliable. Polysemy itself has its own inherent complexities, among these being the problem of determining the exact number of meanings of a polysemous lemma. When the meanings of a polysemous lemma are listed, the central or primary meaning, which is not always easily ascertainable, should come first. A holistic approach is proposed to distinguish polysemy and homonymy, which entails the use of the following criteria: etymology, relatedness vs unrelatedness of meaning, componential analysis, the identification of the central or core meaning and the test of ambiguity. Whatever results are obtained from a particular criterion, these findings must be compared with those of other criteria, and verified against native speakers' intuitive knowledge and introspective judgements.OPSOMMING: Die behandeling van polisemie en homonimie in eentalige algemene woordeboeke met spesiale verwysing na Isichazamazwi SesiNdebele. Hierdie artikel fokus op die behandeling van polisemie en homonimie in algemene eentalige woordeboeke met spesiale verwysing na Isichazamazwi SesiNdebele. Daar is vasgestel dat daar 'n aantal inkonsekwensies in die behandeling van poliseme en homonieme inskrywings in hierdie woordeboek is. Die artikel toon dat 'n te groot steun op een kriterium, veral etimologie, om polisemie en homonimie te onderskei, dikwels misleidend en onbetroubaar is. Polisemie self het sy eie inherente gekompliseerdhede waarvan sommige die probleem is om die presiese aantal betekenisse van 'n poliseme lemma te bepaal. Wanneer die betekenisse van 'n poliseme inskrywing gelys word, behoort die sentrale of primêre betekenis wat nie altyd maklik bepaalbaar is nie, eerste te kom. 'n Holistiese benadering word voorgestel om polisemie en homonimie te onderskei wat die gebruik van die volgende kriteria behels: etimologie, verwantskap teenoor nieverwantskap van betekenis, die identifikasie van die sentrale of kernbetekenis en die toets van dubbelsinnigheid. Watter resultate van 'n bepaalde kriterium ookal verkry word, hierdie bevindinge moet vergelyk word met daardie van ander kriteria, en uiteindelik geverifieer word met moedertaalsprekers se intuïtiewe kennis en introspektiewe oordeel.Sleutelwoorde: POLISEMIE, HOMONIMIE, METAFOOR, KONSEPTUELE BETEKENIS, ETIMOLOGIE, HOMOFONE, HOMOGRAWE, LEMMA, BETEKENIS, INTUÏSIE, INTROSPEKSIE